‘Allegiance … is not so easily translated’: Huguenots, general naturalisation and changing views of allegiance in late seventeenth-century England - Commons, Kathleen (The Huguenot Society journal, 2025)
In 1681, Charles II offered Huguenots fleeing to England the possibility of a ‘general naturalisation’ that would enable them cheaply and easily to become English subjects. This was an unprecedented offer, greeted by the Huguenots with great enthusiasm as all migrants - whether or not they had fled persecution - were legally excluded from English subjects’ rights. However, an act of general naturalisation would not be passed until 1709, and was repealed two years later. The 30-year debate over the possibility, and desirability, of extending general naturalisation has been viewed by historians as primarily relating to the status of migrants in early modern England. This article will recover the ways that the debates about general naturalisation in fact engaged more with the significant changes to, and disputes over, the ways that English subjects’ allegiance was understood in law.